2016
DOI: 10.1002/mds.26533
|View full text |Cite
|
Sign up to set email alerts
|

Lateral geniculate atrophy in Parkinson's with visual hallucination: A trans‐synaptic degeneration?

Abstract: We found microstructural alterations in visual pathways in nondemented PD patients with hallucination, mainly in first-order neurons and atrophy in the lateral geniculate body where the retinal ganglion cells synapse to second-order neurons. Afferent visual pathway degeneration may occur in a trans-synaptic way in PD. Further studies warrant to be conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 43 publications
3
33
0
Order By: Relevance
“…Our finding of white matter changes in posterior thalamic projections is consistent with previous work using tensorderived metrics that showed reduced FA in the optic nerve and optic radiation in an analysis of 5 manually determined regions of interest 34 and increased MD within tracts from the nucleus basalis of Meynert to parietal and occipital regions in patients with PD/VH. 35 In contrast, past whole-brain tensorbased analyses had not revealed any specific white matter changes between PD/VH and PD/non-VH.…”
Section: Discussionsupporting
confidence: 91%
“…Our finding of white matter changes in posterior thalamic projections is consistent with previous work using tensorderived metrics that showed reduced FA in the optic nerve and optic radiation in an analysis of 5 manually determined regions of interest 34 and increased MD within tracts from the nucleus basalis of Meynert to parietal and occipital regions in patients with PD/VH. 35 In contrast, past whole-brain tensorbased analyses had not revealed any specific white matter changes between PD/VH and PD/non-VH.…”
Section: Discussionsupporting
confidence: 91%
“…Studies investigating VH in LBD using more than one approach or imaging technique were included in more than one section of the review and the findings for each technique reported separately in the relevant section. There were eight studies combining different techniques, specifically structural and functional MRI [ 16 , 17 ]; structural MRI and PET [ 18 , 19 ]; structural MRI and DTI [ 20 , 21 ]; structural MRI, DTI, and fMRI [ 22 ]; and fMRI and arterial spin labelling (ASL)-MRI [ 23 ]. Moreover, in two structural MRI studies, different methods were used to investigate regional brain volumes [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the VBM studies described above, other studies have investigated brain morphological features of predefined ROI, especially their overall volume [ 18 , 19 , 20 , 22 , 24 , 41 , 42 ], and shape [ 22 ] in LBD. Three studies examined group differences in cortical thickness using the Freesurfer software package (and adopting thresholds corrected for multiple comparisons) [ 16 , 17 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…in the LGN in conditions where hallucinations are common, such as schizophrenia, have so far been unsuccessful [3,4], though magnetic resonance imaging studies suggest the LGN can be smaller than normal in Parkinson disease [5] and multiple sclerosis [6], disorders in which hallucinations have been described [7,8].…”
Section: Plos Onementioning
confidence: 99%